Experimental optimisation comparison of detonation characteristics between leaded aviation gasoline low lead and its possible unleaded alternatives. (1st December 2020) - Kumar, Thanikasalam; Mohsin, Rahmat; Majid, Zulkifli Abd.; Ghafir, Mohammad Fahmi Abdul; Wash, Ananth Manickam
Highlights: Detonation efficiency of aviation/motor fuels and blends fuels were investigated. Lycoming O-320 engine system with dyno was utilized for search engine optimization employing response surface method. Engine speed, gasoline/blend type and relative detonation index variables were used for optimisation. Research Octane Number 98 fuel provided optimal results of all fuels/blends in this study. 57.153% was the solution with a desirability of 0.759. Abstract: Federal Aviation Administration's twenty years of research with two-hundred unleaded blends has not found a "drop-in" unleaded replacement for aviation gasoline 100 low lead, a specifically formulated fuel for usage in naturally aspirated aircraft engines and contains tetraethyl lead additive to assist on detonation. Tetraethyl lead emission from piston aircrafts can cause serious health impacts and is a human carcinogenic substance. This research optimised the detonation efficiency of 14 aviation/motor fuels/blends. Type of fuels/blends and engine speed were chosen as input parameters. Relative detonation index was the output parameter. The engine speed was differed from 2000 to 2700 and the fuels were changed at fourteen levels. The design matrix consisted of 98 runs and was based on one factor response surface methodology. Analysis of variance was done on the design model to authenticate the significance. Engine speed and type of fuel were set to be in range while relative detonation index was minimised. Confirmation experiment was performed to check and confirm the actual and predicted outcomes. Results showed that at 2300 engine speed, Research Octane Number 98 fuel exhibited the best desirability of 0.759 among all fuels/blends with 57.153% of relative detonation index. The outcome revealed that tetraethyl lead addition into the aviation gasoline low lead can be eliminated.